2011
DOI: 10.2223/jped.2156
|View full text |Cite
|
Sign up to set email alerts
|

The impact of systematic dietary counseling during the first year of life on prevalence rates of anemia and iron deficiency at 12-16 months

Abstract: Objective: To evaluate the impact that a program based on maternal dietary counseling covering breastfeeding and healthy complementary feeding had on the prevalence of iron deficiency, anemia and iron deficiency anemia in children aged 12 to 16 months.Methods: Newborn infants were randomized at birth to an intervention or a control group. Mothers in the intervention group received home visits during the children's first year of life on a monthly basis up to 6 months, and at 8, 10 and 12 months. The mothers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
(21 reference statements)
0
32
0
4
Order By: Relevance
“…The studies were classified into four categories: childcare centres (n 13) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) ; health services (n 4) (26)(27)(28)(29) ; populations in social inequities (n 7) (30)(31)(32)(33)(34)(35)(36) , of which five involved indigenous peoples and two approached Quilombola communities; and population-based studies involving representative samples of Brazilian cities, regions or states (n 13) (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were classified into four categories: childcare centres (n 13) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) ; health services (n 4) (26)(27)(28)(29) ; populations in social inequities (n 7) (30)(31)(32)(33)(34)(35)(36) , of which five involved indigenous peoples and two approached Quilombola communities; and population-based studies involving representative samples of Brazilian cities, regions or states (n 13) (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) .…”
Section: Resultsmentioning
confidence: 99%
“…Although dietary counselling commonly resulted in a better dietary intake profile in targeted subpopulation, such as breastfed for longer and had non-human milk introduced later among infant, consumed more meat and had diets with better iron bioavailability in relation to the children or pregnant women; however, this kind of interventions was not sufficient to prevent occurrence of anaemia, ID or IDA in population with high IDA burden [89][90][91].…”
Section: Improvements In Dietary Diversitymentioning
confidence: 99%
“…Iron reserves at birth are smaller when the mother's reserves are low, reflecting the limited ability of the fetus to acquire iron. A study done in Indonesia with breastfed children aged four to six months found a prevalence of anemia of 37.0% (Hb <10.0 g/dL), having as associated factor the mother's hemoglobin level [27][28][29] .…”
Section: Security Severe Insecuritymentioning
confidence: 99%